Riba-Free Financial Empowerment for Muslim Women: A Path to Sustainable Independence - Zahara, Jihan Nabila; Futaqi, Faruq Ahmad; Chalid, Fitria Idham (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
Introduction: This study analyzes the implementation of BankZiska Ponorogo’s women’s empowerment program through riba-free financing aimed at eliminating riba practices and promoting sustainable economic independence. Research Methods: Using a qualitative explanatory case study, data were collected through interviews, observation, and documentation involving BankZiska’s directors, managers, volunteers, and female beneficiaries. Results: The Al-Qardhul Hasan-based financing provides interest-free, collateral-free capital for women micro-entrepreneurs excluded from formal finance. It improves their income, business stability, and spiritual awareness through mentoring and Islamic financial education, fostering greater confidence and independence. Conclusion: BankZiska’s riba-free model effectively empowers women and promotes inclusive, ethical, and sustainable economic growth. It demonstrates that Islamic social finance can advance financial inclusion, poverty reduction, and gender equality in line with the SDGs.